Criminal justice responses to domestic violence and abuse in England: an analysis of case attrition and inequalities using police data. (14th September 2022) - McPhee, D.; Hester, M.; Bates, L.; Lilley-Walker, S. J.; Patsios, D.
ABSTRACT: Responding to domestic violence and abuse (DVA) poses significant challenges for the criminal justice system, with recent studies highlighting a number of significant gaps and failings in the nature of the police response in particular. This paper reports on findings from a component of the multi-stage ESRC funded project 'Justice, Inequality and Gender-Based Violence' (ESRC grant ES/M010090/1) that relates to 400 reported incidents of DVA involving intimate partners recorded by two police force areas in England in 2014. Drawing on this large data set concerning a wide range of incidents, this paper employs quantitative methods to analyse the trajectories of reports made to the police, and the factors that may influence their progress through, or attrition from the criminal justice system. In doing so, this paper finds that certain 'inequality' factors such as victim gender, vulnerability (including mental health) and incident type are found to impact the progression of cases through the criminal justice system. This work seeks to build on our understanding of what happens to incidents of DVA that are brought to the attention of the police by victims and survivors, and reflects upon how the outcomes of such incidents impact the broader debate concerning the pursuit of a formal, or criminal 'justice' in cases of DVA.